Clinical Supervision To Improve Teachers' Capabilities In The Learning Process At State Elementary School 003 Kepenuhan - Kamsidar Kamsidar (Indonesian Journal of Basic Education, 2021)
The purpose of writing this school action article is to analyze the effectiveness of classroom supervision to improve the ability of teachers in the learning process. The type of research conducted is PTS. The subjects of this study were 10 teachers. The data collection method is document study, and observation. The data analysis method is descriptive and for quantitative data using a supervision instrument. The results obtained from this study are that classroom supervision can improve the ability or professional competence of teachers in learning for teachers at SD Negeri 003 Kepenuhan. This is evident from the process and results obtained in Cycle I, the average increase is to be better, namely 70%. Likewise, in Cycle II, the average increase is even higher, namely 90%. The conclusion obtained from this research is that the combination of classroom supervision and the preparation of school action research can improve the ability or professional competence of teachers in learning